In memoriam: Svitlana Fedorivna Vasylieva (Ukrainian Journal of Ophthalmology, 2025)
Svitlana Fedorivna Vasylieva, a doctor of medical sciences, professor, and ophthalmic surgeon, passed away in Odessa on October 1, 2025, after a long illness. She was 94 years old. She dedicated over 40 years to working at the Odessa Institute of Eye Diseases and Tissue Therapy, named after Academician V.P. Filatov, now known as the State Institution “The Filatov Institute of Eye Diseases and Tissue Therapy of the National Academy of Medical Sciences of Ukraine.”Svitlana Fedorivna Vasylieva was born on August 4, 1931, in Odessa. Her father, Fedir Oleksiyovych Tymchenko, was an agricultural worker, and her mother, Nina Hryhorivna Vasylieva, was a maxillofacial surgeon.In 1956, S. F. Vasylieva graduated from the Odessa Medical Institute and was admitted to the clinical residency at the Filatov Institute of Eye Diseases and Tissue Therapy. She was fortunate to work and study ophthalmology under the guidance of Academician V. P. Filatov for a year until his passing. This experience left an unforgettable impression on her and shaped her future work.Professor Vladimir Shevalov became Svitlana Fedorivna's scientific advisor. Under his guidance, in 1969, S. F. Vasylieva successfully defended her doctoral dissertation, titled “Scleral indentation surgery with catgut implantation for retinal detachment,” which was based on 160 surgical cases she performed. In 1970, following a recommendation by academician N. O. Puchkovskaya, S. F. Vasylieva moved to the Department of Pediatric Ophthalmology under Prof. S. A. Barkhash, a pioneer in national pediatric eye care. There, she researched the causes of blindness and visual impairment in children, examined age-related features of a healthy and diseased child's eye, studied clinical symptoms of major eye diseases and injuries in children, and learned the principles and techniques of their surgical and post-operative restoration as children grow. For 12 years, S. F. Vasylieva led the children's department of the institute and served as the director of the Republican Centre for Children's Vision Protection and the Centre for Eye Microsurgery in Children. Her achievement was that she was the first in Ukraine to introduce endotracheal and nasopharyngeal anesthesia into the practice of pediatric ophthalmic surgery. This enabled the elimination of the lag in pediatric ophthalmic surgery, greatly extended the age range, including infants, for surgical treatment of children, and, most importantly, elevated pediatric ophthalmology to the microsurgical level and introduced the use of laser surgery. This marked a new phase in the development of the institute's paediatric department and enabled the establishment of the Centre for Microsurgery of the Eye in Children, which operated from 1978 to 1991 and held national significance.For the first time in Ukraine, S. F. Vasylieva developed and implemented a method for aspirating cataracts and luxated lenses in children in 1973. She also developed a system of surgical treatment and prevention of retinal detachment in children, using several original techniques, including suture fixation of the retina. She studied the effectiveness of treatment for various forms and degrees of retinal detachment, assessed the success of surgical procedures, and explored the characteristics of retinal detachment in children. She proposed a classification of its main clinical types and developed a system for surgical treatment of rhegmatogenous retinal detachment in children, which was incorporated into S. F. Vasylieva's doctoral dissertation “Surgical treatment of retinal detachment in children and ways to improve its effectiveness” (1984).During this period, the department continued to advance in cataract surgery, retinal detachment, and plastic surgery. Svitlana Fedorivna justified the indications for selecting the most suitable surgical methods for congenital cataracts, iris surgery, and new approaches to treating congenital glaucoma. She devised treatment strategies for malignant eye and orbit neoplasms and introduced original plastic surgery techniques for the eyelids and oculoorbital region, among other contributions. These scientific developments were reported across 117 publications, along with 29 rational proposals, 12 author certificates, and 3 patents for new instruments used in cataract extraction. Additionally, five candidate dissertations supervised by S. F. Vasilyeva include Bulgarian ophthalmologist L. T. Mircheva's work, “Hydrodynamics and hemodynamics of the eye in retinal detachment in children” (1979), Palestinian doctor Abuzeid Shiooli Ahmed's research, “Objective criteria for the selection of surgical intervention for congenital ptosis in children and their clinical evaluation” (1985). The issue of enhancing cosmetic outcomes of eye prosthetics through better formation of the post-nuclear stump was further explored in M. M. Grachev's dissertation, “Formation of the Support-Motor Stump in Eye Removal in Children” (1987). His method for excising cysts, tumors, and foreign bodies in the iridociliary zone received the VDNG medal in 1979.While enjoying her well-earned retirement, S. F. Vasylieva authored several books, including memoirs and a review of academician V. P. Filatov's achievements in ophthalmology titled “In Memory of Academician V. P. Filatov.” She also wrote a book about the final years of academician Filatov and her own impressions of him called “Spiritual and Creative Unity,” as well as a collection of essays about her ophthalmology teacher, Prof. V. E. Shevalov, titled ”Flight with Obstacles," and another memoir. Even while unwell, she refused to give up and dictated a book about her surgical techniques, “Essays on Pediatric Eye Surgery,” specifying which illustrations and photographs should be included. She remained keenly interested in arts, cinema, politics, and enjoyed reading memoirs and detective stories.Colleagues recall Svitlana Fedorivna as principled, precise, attentive to detail, and quick to respond to medical needs, demonstrating expert intuition. As a highly professional, widely erudite, and deeply compassionate person, she earned the well-deserved respect of her colleagues, students, and patients. The Institute's collective extends its condolences to the family and loved ones during this heavy loss. The bright memory of Svitlana Fedorivna will always remain in our hearts. The collective of the State Institution "Institute of Eye Diseases and Tissue Therapy of the National Academy of Medical Sciences of Ukraine"